Pemberian Edukasi Senam Diabetes Pada Ibu-Ibu Lansia Untuk Meningkatkan Kesehatan - Bimo Satrio (STKIP Muhammadiyah Kuningan Secretariat Jurnal Muhammadiyah Untuk Olahraga Indonesia. Building A106 Street of Murtasiah Soepomo No 28b, 45511 Kuningan - West Java Telephone : 0232-874085 Homepage : E-mail, 2023)
The elderly gymnastics service activity aims to provide education about diabetes prevention through the socialization of elderly gymnastics to Aisyiyah Kajen's mothers at the Muhammadiyah Kajen Da'wah Building which was carried out by us students of the Physical Education Study Program, totaling 6 people who had been provided from campus. Alhamdulillah, this socialization activity went smoothly. This socialization was carried out on Saturday, June 25, 2022 at 08.00, the place was in the hall of the Muhammadiyah Kajen Da'wah Building. At the time of the activity the student team of 6 people already had their respective duties including being a gymnastics instructor, there was a section that served as an operator, and there was also a photo documentation.In this activity, participants followed closely how the instructor gave diabetes gymnastics movements, starting from counting the pulse, doing breathing movements, and the core movements of diabetes gymnastics.